Phenotypic divergence and molecular characterization of two sympatric species of genus Barilius (Hamilton) from the River Chenab of Western Himalaya. (13th May 2019) - Singh, Deepak; Kumar, Sumit
Abstract: Barilius bendelisis and Barilius vagra inhabit mostly in the spring‐fed streams of Indian Himalaya and constitute an important portion of protein diet of the rural human population residing near the stream banks. In spite of large aquaculture importance of this genus very less morphometric and molecular studies have been conducted. This study addresses morphometric and molecular characterization of B. bendelisis and B. vagra by using truss analysis and mitochondrial COI gene. A total of 293 samples of Barilius bendelisis and 127 samples of Barilius vagra were collected from three different sites of Chenab river basin from March 2015 to April 2017. 14 landmarks were used to measure 90 truss measurements from digital images of specimens using network of three softwares, tpsUtil, tpsDig2 and PAST. A total of 89 distance variables exhibited significant differences among the populations. The principal component analysis generated ten components explaining 89.164% of total variance among six populations of B. bendelisis and B. vagra . 89.0% of individuals of B. bendelisis and B. vagra were classified into their original groups. The Phylogenetic analysis with other published COI sequences revealed distinct nature of these two species. The study may aid in taxonomic identification and phenotypic divergence which will be helpful in proper conservation and management of these species of hill trout in India.